Effects of oil substrate supplementation on production of prodigiosin by Serratia nematodiphila for dye-sensitized solar cell - Nor Hasmaliana, Abdul Manas; Li, Yee Chong; Yonas Mehari, Tesfamariam; Azham, Zulkharnain; Hafizah, Mahmud; Dayang Salyani, Abang Mahmod; Siti Fatimah Zaharah, Mohamad Fuzi; Nur Izyan, Wan Azelee (Elsevier B.V., 2020)
Bacterial pigments are potential substitute of chemical photosensitizer for dye-sensitized solar cell (DSSC) due to its non-toxic property and cost-effective production from microbial fermentation. Serratia nematodiphila YO1 was isolated from waterfall in Malaysia and identified using 16S ribosomal RNA. Characterization of the red pigment produced by the bacteria has confirmed the pigment as prodigiosin. Prodigiosin was produced from the fermentation of the bacteria in the presence of different oil substrates. Palm oil exhibited the best performance of cell growth and equivalent prodigiosin yield compared to olive oil and peanut oil. Prodigiosin produced with palm oil supplementation was 93 mg/l compared to 7.8 mg/l produced without supplementation, which recorded 11.9 times improvement. Specific growth rate of the cells improved 1.4 times when palm oil was supplemented in the medium. The prodigiosin pigment produced showed comparable performance as a DSSC sensitizer by displaying an open circuit voltage of 336.1 mV and a maximum short circuit current of 0.098 mV/cm2. This study stands a novelty in proving that the production of prodigiosin is favorable in the presence of palm oil substrate with high saturated fat content, which has not been studied before. This is also among the first bacterial prodigiosin tested as photosensitizer for DSSC application.